Membangun Koneksi Individu: Strategi Berbahasa Indonesia Sebagai Alat Penting Komunikasi Interpersonal di Tempat Kerja - Hanafiah, Alya Lubna Putri; Nurrohmah, Alya Novia; Ramdani, Fasya Aulia; Rahmi, Lukita Hediana; Khairunnisa, Ranti Nada; Rizkyanfi, Mochamad Whilky (Indo-MathEdu Intellectuals Journal, 2024)
This study aims to examine the use of Indonesian as a tool to improve the effectiveness of interpersonal communication in the workplace, strengthen work relationships, and create a collaborative work environment.  The method used is qualitative with data collection techniques, namely interviews. Data analysis is carried out qualitatively consisting of data reduction, data presentation, and conclusions. The results of the analysis show that good and appropriate use of Indonesian in the workplace is very important to maintain a level of professionalism, by paying attention to PUEBI guidelines and language structure, and avoiding the use of double, ambiguous words, or terminology unfamiliar to the interlocutor.  The way a person speaks reflects their identity and culture. Interpersonal communication plays an important role in the work environment, affecting productivity and relationships between individuals. Improving interpersonal communication in the office environment involves a variety of strategies, from consistency in language adjustment to participating in activities outside of work hours and maintaining a positive attitude and openness to the opinions of others. Thus, effective interpersonal communication is not only the key to success in the workplace, but also supports the growth and development of both individuals and the organization